Debates literários no jornal A voz de Moçambique entre 1961 e 1964: literatura, censura, racismo: Kufundissana he um tsamba re izwi re Moçambique mumakore ye 1961 ne 1964: Mutauro, kuchoropodza, kurikutondoedza - Alfieri , Noemi (NJINGA e SEPÉ: Revista Internacional de Culturas, Línguas Africanas e Brasileiras (ISSN: 2764-1244), 2023)
The article dwells on cultural debates that took place, between 1961 and 1964, in the literary page «Artes e Letras» of the newspaper A voz de Moçambique, with focus on the critics to salazarist censorship, on the idea of Mozambican literature in opposition to literatura ultramarina (“overseas literature”) and on racism. It will especially focus on disputes. The first - originated from Rodrigues Júnior’s declarations on the existence of a literatura ultramarina, instead of Mozambican literature - resulted in a well-known polemic that opposed Rui Knopfli and Eugénio Lisboa to Alfredo Margarido.The second, that was initially published in the journal A tribuna, was between José Craveirinha and Sacadura Falcão. In that occasion, the mozambican writer desmantled racists thesis, defending cultural dignity of black people, as well as non-western cultural traditions. **** Patchiguagua tchigo tchicha unza Machoco ye tsika dzakaphasiswa mumakore ye 1961 ne 1964, zviri pepha ne matauro, kuita, kunyora Ne Masoko yenguwa mu izwi re Moçambique zvirimukati me kuchoropodza, kurikutondoedza vzakavisua ngue Salazarista, Pafungua dzecutondoedza maitire ye adzari ye Moçambique, kurikusiya maitire ye ngua yakapinda, tingati ye racismo. Kurikupa muezanisso ne makuikui Mair, ye kutanga mahonere ya Rodrigues Júnior pamaererano ye maitire yekarekare.Virimukati me ma erenguerue hanyamasi munhika ye Moçambique, zvakabhara botso zvakazobara mukuti Rui Kropfli na Eugénio Lisboa azonde Alfredo Margarido.Ye Tchipire yakabunisua pahmene mu buco remasoco A Tribuna, zvakaizua ndi José Craveirinha na Sacadura Forcão, pangua yekuti munyori we Moçambique waipanguidza mafunguire ye ma racista, kuriku Kutenderana ne Tsika dze maboi ne Tsika dzepasitchigare dzisiripi dze Nhica dze azungu.